Funkcjonowanie elektronicznych zamówień publicznych na przykładzie Polskiej Platformy Przetargowej - Galewski, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Public procurement is an important sector of the European economy. Public sector expenditure accounts for 16% of the Community GDP. The procurement process itself is complex, time consuming and slow, therefore EU countries are currently looking for new solutions to simplify the existing legal framework and encourage the use of electronic procedures. The Polish Procurement Platform was created in 2003 in the Polish Security Printing Works. It is a complex system that takes care of electronic tenders and purchases organization. It offers e-bidding, e-auctions, e-catalogues and additional services, such as trainings and consulting. Main benefits of tenders and purchases made via electronic procurement platform are significant cost reduction and the clarity of the proceedings. Modernization of public sector procurement process can also serve as a key driver of e-business adoption across the economy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 101-111